FINTECH ACCESS AND DIGITAL FINANCIAL LITERACY ON FINANCIAL BEHAVIOR IN THE DIGITAL ERA: THE MEDIATION ROLE OF FINANCIAL SELF-CONTROL - Adielyani, Dea (STIE AMA Salatiga, 2025)
ABSTRACT : This study aims to examine the impact of fintech access and digital financial literacy on financial behavior, as well as the mediating role of financial self-control in this relationship. The study adopts a deductive approach and employs a quantitative survey design for data collection and analysis. Data were collected through an online questionnaire administered to 175 Generation Z respondents in Semarang. The analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The findings indicate that fintech access and digital literacy have a significant influence on financial behavior. Furthermore, fintech access, digital financial literacy, and financial self-control jointly affect financial behavior. The results also confirm that financial self-control plays a mediating role, acting as an indirect mechanism through which fintech access and digital financial literacy influence financial behavior. From a theoretical perspective, this study highlights the crucial role of self-control in strengthening the effects of fintech access and digital financial literacy on financial behavior in the digital financial era. From a managerial perspective, the findings suggests that improving digital financial literacy can enhance financial behavior, and therefore universities are encouraged to optimize financial education through various educational initiatives for students.ABSTRAK : Penelitian ini bertujuan untuk menganalisis dampak akses Fintech dan literasi keuangan digital terhadap perilaku keuangan. Penelitian ini juga bertujuan untuk menganalisis dampak akses Fintech dan literasi keuangan digital terhadap perilaku keuangan dengan peran mediasi pengendalian diri keuangan. Penelitian ini mengikuti pendekatan deduktif dan menggunakan strategi survei kuantitatif untuk pengumpulan dan analisis data. Survei daring berfungsi sebagai metode untuk mengumpulkan tanggapan dari peserta. Penelitian ini melibatkan ukuran sampel 175 Gen Z di Semarang. Penelitian ini menggunakan teknik PLS SEM. Temuan menunjukkan bahwa akses Fintech dan literasi keuangan digital memengaruhi perilaku keuangan. Lebih lanjut, akses Fintech, literasi keuangan digital, dan pengendalian diri keuangan memengaruhi perilaku keuangan. Kesimpulan yang dapat ditarik adalah bahwa pengendalian diri keuangan menunjukkan peran mediasi sebagai efek tidak langsung pada faktor-faktor tersebut. Sebagai implikasi teoritis, penelitian saat ini memberikan kontribusi terhadap literatur teoritis dengan menyoroti peran penting pengendalian diri dalam meningkatkan pengaruh akses Fintech dan faktor literasi digital terhadap peran keuangan di era keuangan digital. Implikasi manajerial bahwa peningkatan literasi keuangan digital mendorong perilaku keuangan adalah bahwa universitas mengoptimalkannya melalui berbagai inisiatif pendidikan bagi mahasiswa.